Assessing Motivations for Nonprescribed Buprenorphine Use Among Rural Appalachian Substance Users. Issue 1 (30th January 2023) - McDonald, Madelyn J.; DeVeaugh-Geiss, Angela M.; Chilcoat, Howard D.; Havens, Jennifer R.
Abstract : Objective: Buprenorphine (Suboxone) is an effective treatment for opioid use disorder (OUD). However, there have been widespread reports of diversion and misuse. This study examined motivations for nonprescribed buprenorphine use among rural residents. Methods: Eligible participants (N = 200) were at least 18 years old, had used any illegal or prescription drugs to get high, and had ever used nonprescribed buprenorphine. A questionnaire administered by a trained interviewer assessed demographic characteristics, substance use, and motivations for use. Results: Primary motivations for first nonprescribed buprenorphine use included avoiding withdrawal and getting high, while at most recent nonprescribed use, motivations shifted toward maintaining abstinence from other drugs. In adjusted logistic regression analyses, past month use of stimulants decreased odds of nonprescribed buprenorphine use for the purposes of self-treatment by 68% (adjusted odds ratio, 0.26; 95% confidence interval, 0.11–0.61), whereas history of treatment for OUD more than doubled odds of use for self-treatment (adjusted odds ratio, 2.71; 95% confidence interval, 1.11–6.63). Conclusions: Results indicate that many individuals used buprenorphine without a prescription, motivated largely by behaviors consistent with self-treatment, and diversion of buprenorphine may be driven by these motivations more than desire to get high. While many participants attempted to access treatment, many were still using nonprescribed buprenorphine for self-treatment, and many were dissatisfied with care they had received as part of a treatment program. Thus, increasing quantity of providers may not be adequate to address the opioid epidemic, but particular attention should be paid to providing care targeted to the needs of those with OUD in rural areas.